Tinjauan Tentang Pengajuan Kasasi Penuntut Umum Atas Dasar Tidak Diterapkannya Hukum Sebagaimana Mestinya Oleh Judex Factie Dalam Perkara Pencucian Uang - Kristian, Otniel Yustisia (Sebelas Maret University, 2017)
Reviewing the case of money laundering were done collectively together by The Defendants Raden Mas Johanes Sarwono, S.H., Ir. Stefanus Farok Nurtjahja, and Umar Muchsin, The Panel of Judges in Jakarta Pusat District Court has made decision that stated The Defendants be clear from all demands. In its consideration, Judex Factie stated that the actions of The Defendants is civil actions on the basis of agreements as the ties between them. And then, The Public Prosecutor filling Cassation to The Supreme Court with reason Judex Factie did Not Apply The Law As It Should Be. In The Memory of Cassation, The Public Prosecutor argued that the agreement only as a basic justification for The Defendants to commit the crimes. Based on the description, The Author is interested to review The Supreme Court Number: 535K/Pid.Sus/2014 to determine whether the filing Cassation from The Public Prosecutor with reason Judex Factie Did Not Apply The Law As It Should Be in the case of money laundering is in conformity with the provisions of Article 253 Criminal Procedure Code. The types of research is doctrinal legal research, with research approach is case approach, and the law materials analysis techniques is using legal reasoning by deduction. Based on research by the author, the author found result that the filling Cassation from The Public Prosecutor with reason Judex Factie Did Not Apply The Law as it should be in the case of money laundering is conformable with the provisions of Article 253 Criminal Procedure Code. In this case Judex Factie had misapplied the law by ignoring the legal facts that revealed at the court. Keywords: The Filing Cassation From The Public Prosecutor, Failure To Apply The Law As It Should Be, Judex Factie, Money Laundering